PENINGKATAN HASIL BELAJAR MAHASISWA PADA MATA KULIAH KIMIA DASAR II DENGAN MENGGUNAKAN PETA KONSEP BERORIENTASI CHEMOENTREPRENEURSHIP (CEP) - Nurhayati, Sri; Subroto, Tjahyo (Jurnal Penelitian Pendidikan, 2012)
Based on the questionnaire to 52 students UNNES Department of Chemistry Faculty, teaching methods of lectures and lecturers are still such things are very boring for students. Moreover, the course material is primarily Basic Chemistry subjects that are less desirable and considered difficult by students because it is abstract, so it needs to be assisted visualization. It is therefore interesting to study as well as creativity and innovation fostering student learning and not so monotonous. The purpose of this study to determine the increase in the chemical and life skill learning of students with learning models CEP. This research is a class action that was implemented in three cycles. Each cycle consists of planning, implementation, observation, and reflection. The subjects of this study were students of Chemistry Department of Education UNNES the second half. The focus is investigated in this study is the result of learning and life skill development of students. The data obtained and analyzed using descriptive methods to determine the increase in the learning and life skill development of students. From the research, studying classical completeness increased from cycle I (44%), cycle II (82%), and cycle III (87%). The average scores of students cycle life skill I, II, and III, respectively 77%, 80% and 92% .. Based on these results we can conclude that the results of student learning and life skill can be improved through the implementation of CEP learning model.